Frameshift variation in the HMG-CoA reductase gene and unresponsiveness to cholesterol-lowering drugs in type 2 diabetes mellitus patients - Esmat Khaleqsefat; Khder Hussein Rasul; Ramiar Kamal Kheder; Sonia Baban; Jamil Baban (Scientific Reports)
Abstract Dyslipidemia, an imbalance in blood lipid levels, is a frequent complication of type 2 diabetes mellitus (DM2) and heightens the risk of cardiovascular diseases (CVDs). Statins, which inhibit 3-hydroxy-3-methylglutaryl-CoA reductase, are potent competitive inhibitors that reduce plasma cholesterol levels. However, individual responses to statins can vary markedly, possibly due to genetic variations in the 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) gene. This study aimed to investigate the pharmacogenetic relationship between the HMGCR gene and hypercholesterolemia in type 2 diabetes mellitus patients who respond differently to atorvastatin, as well as in healthy individuals. Ninety participants were involved, including sixty with type 2 diabetes mellitus and hypercholesterolemia, and thirty healthy individuals. They were randomly assigned to three groups: responsive (received atorvastatin 40 mg), non-responsive (also received atorvastatin 40 mg), and control. Both responsive and non-responsive groups underwent fasting. Biochemical tests were conducted, followed by genetic analysis to identify mutations in the HMGCR gene. The effects of statins in each group were assessed using analysis of variance (ANOVA) and post hoc Tukey’s Honestly Significant Difference (HSD) analysis. Atorvastatin 40 mg was administered to assess its efficacy in reducing cholesterol levels in patients with hypercholesterolemia and type 2 diabetes mellitus. The control group exhibited similar cholesterol levels to the responsive group (cholesterol < 200 mg/dl). However, both control and responsive groups significantly differed from the non-responsive group, which had markedly elevated cholesterol levels (> 240 mg/dl). Genetic analysis revealed a cytosine nucleotide insertion in the catalytic domain of the HMGCR gene in only two non-responsive participants to atorvastatin 40 mg therapy. These two patients showed non-responsiveness to atorvastatin 40 mg due to a genetic mutation in the HMGCR gene. This mutation altered the amino acid sequence in the flap domain, replacing isoleucine with a stop codon. As a result, translation was prematurely terminated, leading to the production of truncated proteins.